Education inequalities and human capital formation in MENA region - (:unkn) unknown (IGI Global, 2018)
This chapter examines education system and education development in MENA region and compare to other selected region in the frame of human capital. It also focus on issue of education quality and inequality. In here, human capital is identified and measured by using education-based factors such as drop-out rates, repetition rates, literacy rates and international test scores, enrollment rates. The results of analysis show that the student participation is common with high enrollment rates and most governments in the region have announced large expenditures on education. Despite impressive gains in the participation of student in the different academic level and intensive public expenditures on education in the region, MENA region suffer from many problems regarding education such as, poor efficiency, low quality, illiteracy and gender inequality, low labor force participation of female. As a results, MENA governments should improve education systems to focus on not only on increasing enrollments, but also on improving the quality of education. © 2019 by IGI Global. All rights reserved.